(8x−7)(8x−5)(2x−1)(4x−1)=9
⇔(8x−7)(8x−5)(4x−4)(8x−2)=72
Đặt a = 8x - 5, ta được:
(a−2).a(a+1)(a+3)=72
⇔a4+4a3+3a2−2a3−8a2−6a−72=0
⇔a4+4a3−2a3−8a2+3a2+12a−18a−72=0⇔(a4+4a3)−(2a3+8a2)+(3a2+12a)−(18a+72)=0
⇔a3(a+4)−2a2(a+4)+3a(a+4)−18(a+4)=0 ⇔(a+4)(a3−2a2+3a−18)=0
⇔(a+4)(a3−3a2+a2−3a+6a−18)=0
⇔(a+4)[(a3−3a2)+(a2−3a)+(6a−18)]=0
⇔(a+4)[a2(a−3)+a(a−3)+6(a−3)]=0
⇔(a+4)(a−3)(a2+a+6)=0
Ta có: a2+a+6=a2+2.a.21+41+423=(a+21)2+423
(a+21)≥0
Suy ra (a+21)2+423>0
=> a2 +a+6 = 0 (loại)
Suy ra: a = -4 hoặc a=3
Với a = -4, ta được:
8x - 5 = -4
=> x = 81
Với a = 3, ta được:
8x - 5 = 3
=> x = 1